2005
DOI: 10.1105/tpc.104.027516
|View full text |Cite
|
Sign up to set email alerts
|

CRS1, a Chloroplast Group II Intron Splicing Factor, Promotes Intron Folding through Specific Interactions with Two Intron Domains

Abstract: Group II introns are ribozymes that catalyze a splicing reaction with the same chemical steps as spliceosome-mediated splicing. Many group II introns have lost the capacity to self-splice while acquiring compensatory interactions with hostderived protein cofactors. Degenerate group II introns are particularly abundant in the organellar genomes of plants, where their requirement for nuclear-encoded splicing factors provides a means for the integration of nuclear and organellar functions. We present a biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 44 publications
0
106
0
Order By: Relevance
“…Several in vitro experiments have shown that the ion concentration can be lowered if specific proteins are added that stabilize the RNA structure (Gampel and Cech 1991;Caprara et al 1996;Matsuura et al 1997;Weeks 1997;Ostersetzer et al 2005) and that can bind folding intermediates (Caprara et al 1996). This has also been confirmed by several in vivo experiments (Mohr et al 1992;Waldsich et al 2002a,b).…”
Section: Protein-rna Interactionsmentioning
confidence: 83%
“…Several in vitro experiments have shown that the ion concentration can be lowered if specific proteins are added that stabilize the RNA structure (Gampel and Cech 1991;Caprara et al 1996;Matsuura et al 1997;Weeks 1997;Ostersetzer et al 2005) and that can bind folding intermediates (Caprara et al 1996). This has also been confirmed by several in vivo experiments (Mohr et al 1992;Waldsich et al 2002a,b).…”
Section: Protein-rna Interactionsmentioning
confidence: 83%
“…Several lines of evidence support the idea that CRM domains bind RNA: (1) all three characterized CRM domain proteins in plants (CRS1, CAF1, and CAF2) are associated with RNA in vivo and influence RNA metabolism (Till et al 2001;Ostheimer et al 2003); (2) recombinant CRS1 binds with high affinity to its cognate group II intron RNA in vitro (Ostersetzer et al 2005); (3) E. coli YhbY is bound in vivo to pre-50S ribosomal subunits (see above), whose surface is composed largely of RNA (Ban et al 2000;Yusupov et al 2001); and (4) structural studies of several YhbY orthologs revealed structural similarity to known RNA binding domains and a putative RNA binding surface (Ostheimer et al 2002;Willis et al 2002;Aravind et al 2003;Liu and Wyss 2004). In addition, CRM domains share an intriguing similarity with the KH RNA binding domain: a six amino acid motif, ''GxxG'' flanked by large aliphatic residues, within which one ''x'' is typically a basic residue (Fig.…”
Section: In Vitro Rna Binding Activity Of An Isolated Crm Domainmentioning
confidence: 87%
“…A search for known functional motifs detected a predicted coiled-coil domain preceding the third CRM domain in all members of the CRS1 subfamily (Fig. 6); this region might mediate homo-or heterodimerization, including, potentially, the homodimerization reported for recombinant CRS1 (Ostersetzer et al 2005).…”
Section: Expansion and Diversification Of The Crm Domain Family In Plmentioning
confidence: 99%
“…Among assayed chloroplast introns in Arabidopsis and maize, crs1 is a required specific cofactor for the atpF intron where it promotes intron folding (Jenkins et al 1997;Vogel et al 1999;Ostersetzer et al 2005;Asakura and Barkan 2006). Intron recognition by crs1 has been mapped to elements of specific intron domains in maize (Ostersetzer et al 2005), although these are not highly conserved either across angiosperms or in the Malpighiales sequenced here. Lack of splicing of the spinach atpF intron in transgenic Chlamydomonas suggests host factors are also taxon specific (Deshpande et al 1995).…”
Section: Evolution Of Atpf and Loss Of Its Intronmentioning
confidence: 88%